Manejo e composição químico-bromatológica de Pilosocereus gounellei, em caatinga no sertão cearense - Magalhães, Regina Maria Fontenele (2014)
This work was carried out to monitor the growth and the shoots of Pilosocereus gounellei in Ceará Caatinga and check whether there were differences in the chemical composition of xiquexique handled in different ways, as the withdrawal of thorns, stored in the shade of a tree or in a shed for 31 days. The experiments were performed in New Barra district, Tauá, Ceará. In the first experiment the experimental design was completely randomized, with three treatments and 40 plants per repetition. The treatments were: T1 - Plant unbranched (control); T2 - Plant with a primary branch and T3 - Plant with two primary branches. We randomly selected 120 plants xiquexiques in approximately one hectare of scrub. For selection were used xiquexiques which estimates the initial ones, to the diameter of the stems (DC), were 62.4 ± 2.9 mm; to the diameter of the primary branches 1 (DR1) were 52.9 ± 3.1; for the average diameter of the primary branches 2 (DR2) were 47.8 ± 4.2 mm. In relation to the length, the initial steps of the primary branch 1 (CR1) were 630 ± 210 mm and the length of the primary arm 2 (CR2) was 580 ± 164 mm. After the selection has been made the standardization of plants with manual cuts, leaving them with a height of 50 cm (main stem length). Then the treatments was conducted: the T1 treatment all branches were removed, leaving only the main stem; in T2 treatment was left only one primary branch and on T3 were left two primary branches. To make the standardization of cuts and application of plant treatments pruning shears was used. Each plant was an experimental unit, which were identified with zinc plates, tied with wire, consisting treatment and experimental unit. They were measured every month the diameter and length of the main stem and shoots. Data were collected monthly between February 2013 and February 2014. It was observed that most of the shoots, regardless of treatment emerged in the basal region and the most developed were the primary treatment without branching. it was found that the treatment in which it was left only a branch plant developed in a shorter period of time. The second experiment was carried out for seven from October to November 6, 2013. The experimental design was a split plot in time, with three replicates per treatment. Were selected at random, 320 plant xiquexiques in the study area in a radius of about 10 ha, with uniform characteristics. For the choice of plants were used certain criteria, such as height, crown diameter, stem diameter at ground level and the amount of primary branches. After this selection were withdrawn 960 primary branches with approximately 40 cm long. Then they were transported in a truck to the warehouse, sorted and separated, 240 branches for each treatment. The plots were the storage locations (1: Tree and 2: shed) and the subplots were represented by four types of disposal of thorns processing (1: in natura with aculeus control); 2: use of flamethrower during storage; 3: burns in coivara during storage; 4: Xiquexique submitted to burning the thorns in launches calls upon the withdrawal of the sample evaluated during 31 days. It was observed that the storage location did not influence the results, can be done either under the tree as in a shed with air intake. It has been found that the Xiquexique should be stored in natura and removal of the spines should only be done in the preceding hours use, it was observed that there was no loss in nutritional content of the plant. In addition to being stored for a period of 31 days. Greater amount of Xiquexique can be harvested regardless of its immediate use, reducing the costs involved in cutting activities and transportation.